Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $1<p<\infty$ and $f,g \in L^p (X,M,\mu)$. Where $||f||_P$ and $||g||_p$ are non zero, and $||f+g||_p = ||f||_p +||g||_p$ .

Proving that equality: $${f \over ||f||_p} = {g \over ||g||_p} \text{ }\mu -a.e.$$

What theorem is available for that prove? I can't find start point.

share|cite|improve this question
See this – leo Jun 14 '12 at 4:04
@leo: while t.b.'s answer there can be moved this way to get an answer, I don't think they are exactly dupes. – Willie Wong Jun 14 '12 at 9:18
@WillieWong I just realized that this is about Minkowski's inequality. I have read the question too fast. Sorry about that. You are right this a good question in his own right. However, the conditions to equality in Minkowski's inequality are the same of Hölder's inequality. – leo Jun 14 '12 at 16:11
up vote 2 down vote accepted

The triangle inequality (Minkowski) is proven using Hölder. To show what you want, you can repeat that argument:

(note that $q(p-1)=p$)

$$ \|f\|_p+\|g\|_p=\|f+g\|_p=\left(\int|f+g|^p\right)^{1/p}=\left(\int|f+g|\,|f+g|^{p-1}\right)^{1/p}\leq\left(\int|f|\,|f+g|^{p-1}+\int|g|\,|f+g|^{p-1}\right)^{1/p} \leq\left(\|f\|_p \left(\int|f+g|^p\right)^{1/q}+\|g\|_p \left(\int|f+g|^p\right)^{1/q}\right)^{1/p} =\left((\|f\|_p+\|g\|_p)\left(\int|f+g|^p\right)^{1/q} \right)^{1/p} =\left(\|f+g\|_p \|f+g\|_p^{p/q} \right)^{1/p} =\left(\|f+g\|_p \|f+g\|_p^{p-1} \right)^{1/p} =\left( \|f+g\|_p^{p} \right)^{1/p} =\|f+g\|_p=\|f\|_p+\|g\|_p $$

In particular we have equality in the two Hölder inequalities we used in the middle (the second "$\leq$"). Equality in Hölder occurs only when the $p$ and $q$ powers of the two factors are linearly dependent. This means that there exist constants $\alpha,\beta$ such that $$ |f|^p=\alpha|f+g|^{q(p-1)},\ \ |g|^p=\beta|f+g|^{q(p-1)} $$ almost everywhere.

So $|g|^p=\gamma|f|^p$ a.e. for some constant $\gamma$, and then $|g|=\delta|f|$ a.e. for yet another constant. Then $$ \frac{|f|}{\|f\|_p}=\frac{|g|}{\|g\|_p}\ \ \ \text{a.e.} $$

share|cite|improve this answer
Perfect answer. Thanks @MartinArgerami – Collins Jun 13 '12 at 5:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.